Analysis of kinematic patterns in runners. An approach based on inertial sensors and functional data analysis - Medina, E.; Palomares, N.; Page, A.; Bazuelo-Ruiz, B. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The aim of this study was to define a methodology able to analyse the foot motion using an inertial measurement unit (IMU) integrated in the midsole of the running shoe. Nineteen subjects performed two tests: an incremental running test in order to determine their individual anaerobic threshold (IAT) and, 2-7 days later, a constant-speed test according to their speed at IAT. The foot motion at the sagittal plane was analysed using Functional Data Analysis (FDA) techniques. This methodology enables to determine the variations in the runners´ steps comparing two fatigue states.